MICROFACIES AND ORIGIN OF SOME ARCHEAN CHERTS (PILBARA, AUSTRALIA) - Orberger B.; Rouchon V.; Hashizume K.; Westall F.; De Vries S.T.; Pinti D.L.; Wagner C.; Wirth R. (My University, 2006)
Four cherts sampled in the East Pilbara craton (Western Australia) at Marble Bar (Towers Formation), North Pole Dome (Dresser and Apex Basalt Formation), and Kittys Gap (Panorama Formation) were studied for micro- and nanomineralogy and geochemistry to determine their protoliths and to provide new insights on the physico-chemical and biological conditions of their depositional environments. The Marble Bar chert was formed at the interface with a basaltic rock. Hydrothermal fluids leached major and trace elements from the basalt and silicified the protolith of this chert. The elements Fe, Mn, Si, Ca, Mg, REE, Au, Pd, Cr, and Ni precipitated as a microbanded iron formation (BIF) under reducing and alkaline conditions. The chert is composed of magnetite, carbonates, and quartz and forms a stromatolite-like structure. Later oxidizing fluids replaced magnetite and carbonates with Fe-Mn oxyhydroxides. They show vermicular microtextures and filamentous nanotextures. Each filament is composed of euhedral nanoscopic hematite. These oxides contain several thousands of ppm of N and C, and measured C/N ratios are similar to those observed in organic matter preserved in marine sediments, thus suggesting an organic activity. Two black cherts from hydrothermal dykes of the North Pole Dome are interpreted as having had a black shale precursor, based on the REE (rare earth elements) and trace metal characteristics. These rocks were probably entrained into the dykes and hydrothermally overprinted. Although these two cherts had the same history, the physico-chemical conditions differed during their formation. The chert from the chert-barite unit of the Dresser Formation was formed under reducing and alkaline conditions. This is clearly indicated by clusters of nanosulfide spherules replacing precursor minerals; weblike Fe-sulfides intergrown with sphalerite; As-pyrite and vaesite; and the presence of carbonates. The black chert from the Apex Basalt Formation was formed under oxidizing conditions, as indicated by clusters of nanospherules of Fe-oxides and a negative Ce anomaly. A black and white laminated chert from Kittys Gap was formed in a shallow marine to subaerial environment, by silicification of a rhyodacitic volcaniclastic rock. This process was accompanied by the development of microbial mats on the sediment surfaces and the formation of microbial colonies around precursor K-feldspars, Ti-bearing biotites, amphiboles, and ghost spherulites. The environment was slightly oxidizing, as indicated by the negative Ce anomaly and the presence of Ti-oxides. The presence of K-bearing phyllosilicates rather than K-feldspars indicates that the environment was also slightly acidic. Elevated Cu and Zn contents in the black laminae point to a limited influence from hydrothermal fluids. The silica probably originated mainly from alteration of the minerals of the volcaniclastic rock due to diagenetic alteration by seawater. © 2006 Geological Society of America.
Keywords: ARCHAEAN SEDIMENTS; BANDED IRON FORMATIONS; CHERT; IRON OXYHYDROXIDES; MICROBIAL ACTIVITY; Archean; Precambrian::Archean; Докембрий::Архей